New Canadian library : the Ross-McClelland years, 1952-1978 - Friskney, Janet Beverly, 1968- (Studies in book and print culture., 2007)
"In New Canadian Library, Janet B. Friskney takes the reader through the early history of the NCL series, focusing on the period up to 1978 when Malcolm Ross retired as general editor. A wealth of archival resources, published reviews, and NCL volumes themselves are used to survey the working relationship between Ross and McClelland, as well as the collaborative participation of those who, through the middle decades of the twentieth century, were committed to studying and nurturing Canada's literary heritage. To place the New Canadian Library in its proper historical context, Friskney examines the simultaneous development of Canadian literary studies as a legitimate area of research and teaching in academe and acknowledges the NCL as a milestone in Canadian publishing history."--Jacket